831 Pain Networks Connectivity Changes Following the Relief of Prolonged Cancer Pain. (1st April 2022) - Berger, Assaf; Jalon, Itamar; Gonen, Tal; Shofty, Ben; Tellem, Rotem; Hochberg, Uri; Artzi, Moran; Ben-Bashat, Dafna; Hendler, Talma; Strauss, Ido
Abstract : INTRODUCTION: The "salience network" is normally engaged in humans' response to acute internal or environmental stimuli, including pain. It comprises connections between the anterior insula (AI) and dorsal anterior cingulate cortex (dACC), among others. Chronic pain conditions have been associated with abnormally increased functional connectivity (FC) within the salience network in comparison to healthy individuals. METHODS: We prospectively followed patients that underwent cervical cordotomy (n=15) and cingulotomy (n=11) for relief of intractable oncological pain during the years 2016-2019. All patients did resting-state functional Magnetic Resonance Imaging (rsfMRI) before and after the procedures. Clinical data was collected, including pre- and post-operative numeric rating scale (NRS) pain scores. RESULTS: All patients (aged 62±11) reported a significant improvement in their pain from NRS 9±1 to 1±1 in cordotomy (p=0.001) and 2±3 in cingulotomy (p=0.005). By comparing pre- and post-operative rsfMRI scans, we demonstrated a significant decrease in the FC between components of the salience network following both cordotomy (p=0.007) and cingulotomy (p=0.009). In the cordotomy group we found a significant decrease in the connectivity between the thalamus and dACC (p=0.019) and within the sensory-motor cortex (p=0.003). CONCLUSIONS: Surgical interventions along the pain pathways can lead to a sudden relief of chronic pain in parallel to a significant decrease in the functional connectivity within pain related networks.